Pakistan’s Search for Security through Reliable Balance of Power and Nuclear Weapons - Hassan Masood (Journal of Political Studies, 2018)
At the time of independence Pakistan faced severe insecurity emanating from a fractured geography, non-existent constitutional framework, weak economy, and military capability in the face of an overwhelmingly powerful and hostile India. The paper explores Pakistan’s efforts for establishing a reliable balance of power with India first by joining the collective security later supplementing it by joining alliances. It argues that the secession of East Pakistan was the turning point establishing the unreliability of the erstwhile basis of balance of power, leading Pakistan to the development of nuclear weapons as a reliable basis for a Pakistan-India balance of power while retaining the earlier two bases.